A Conceptual Framework for Studying and Investing in Precision Nutrition - Zeisel, Steven H. (Frontiers in Genetics, 2019)
Nutrients and food-derived bioactive molecules must transit complex metabolic pathways, and these pathways vary between people. Metabolic heterogeneity is caused by genetic variation, epigenetic variation, differences in microbiome composition, and by environmental exposures. The review discusses a number of these sources of metabolic heterogeneity and presents some of the research investments that will be needed to make applications of Precision Nutrition practical.